2008
DOI: 10.1007/s10664-008-9074-8
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the relationship between team climate and software quality—a quasi-experimental study

Abstract: This paper describes an empirical study that examined the work climate within software development teams. The question was whether the team climate in software developer teams has any relation to software product quality. We define team climate as the shared perceptions of the team's work procedures and practices. The team climate factors examined were West and Anderson's participative safety, support for innovation, team vision and task orientation. These four factors were measured before the project using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 47 publications
1
46
0
Order By: Relevance
“…The second part focuses on the study of team climate [5][6][7] with respect to product quality and software development team member satisfaction in the quasi-experimental study. This research is reported in detail in Acuña et al [2]. In the following sections we describe the goals, hypotheses, variables, participants, subjects, measurement instruments, and quasi-experimental procedure of the three studies.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second part focuses on the study of team climate [5][6][7] with respect to product quality and software development team member satisfaction in the quasi-experimental study. This research is reported in detail in Acuña et al [2]. In the following sections we describe the goals, hypotheses, variables, participants, subjects, measurement instruments, and quasi-experimental procedure of the three studies.…”
Section: Methodsmentioning
confidence: 99%
“…They conclude hence that empirical studies require replication to consolidate knowledge that is potentially useful for new research and is likely to influence software engineering practice. The research reported here presents a meta-analysis of replications that we have conducted of the baseline experiment [2,3].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…They are actually responsible for ensuring the quality of the application [21]. End users are there to provide direction of what needs to be done as part of the project [22] and they are the main reason why an SDP is conducted. The main purpose of conducting SDPs is to address the challenges the end users are facing [1].…”
Section: Different Stakeholders For Software Development Projectsmentioning
confidence: 99%
“…Although no direct effect was found between team climate and the other output factors examined in this study, the findings showed the presence of an indirect effect of team climate on all three output factors through team commitment. Most studies (Acuna, Gomez, & Jouristo, 2008;Blansett, 2003;Fox & Mohapatra, 2007) that have examined the influence of team climate on performance did not examine the mediating effect of a third variable. Hence, the influence of team climate on team performance found in those studies may be due to process factors such as team commitment.…”
Section: Discussionmentioning
confidence: 99%